Brain involvement in systemic immune mediated diseases: magnetic resonance and magnetisation transfer imaging study. Issue 2 (1st February 2000) - Rovaris, M; Viti, B; Ciboddo, G; Gerevini, S; Capra, R; Iannucci, G; Comi, G; Filippi, M
Abstract : OBJECTIVE: Magnetisation transfer imaging (MTI) provides information about brain damage with increased pathological specificity over conventional MRI and detects subtle abnormalities in the normal appearing brain tissue, which go undetected with conventional scanning. Brain MRI and MTI findings were compared in patients with multiple sclerosis (MS) and systemic immune mediated diseases (SIDs) affecting the CNS to investigate their roles in understanding the nature of brain damage in these diseases. METHODS: Brain dual echo, T1 weighted and MTI scans were obtained in patients affected by systemic lupus erithematosus (SLE) with (NSLE, n=9) and without clinical CNS involvement (n=15), Behçet's disease (BD) (n=5), Wegener's granulomatosis (WG) (n=9), and antiphospholipid antibody syndrome (APLAS) (n=6). Ten patients with clinically definite MS and 15 healthy controls also underwent the same scanning protocol. Brain MRI and MT ratio (MTR) images of the same subject were coregistered and postprocessed to obtain MTR histograms of the whole brain and of the NABT. RESULTS: Brain hyperintense lesions were found in all patients with MS and with NSLE and in 5/15 patients with SLE, 5/9 with WG, 1/5 with BD, and 3/6 with APLAS. The lesion burden in the brain was significantly higher in patients with MS compared with all the other disease groups. All MTR histogram parameters were significantly different among patient subgroups. Patients with MS had significantly lower average MTR than all except patients with NSLE and significantly lower peak height and location than patients with SLE. patients with NSLE had significantly lower average MTR than patients with SLE. CONCLUSIONS: Microscopic brain tissue damage is relevant in patients with MS, but, apart from patients with NSLE, it seems to be absent in systemic immune mediated diseases, even in the presence of macroscopic MRI lesions or clinical evidence of CNS involvement.